AL-FARABI'S PHILOSOPHY ABOUT THE MAIN COUNTRY (AL-MADINAH AL-FADHILAH) - Nuthpaturahman Nuthpaturahman (Jurnal Ilmiah Ilmu Pendidikan dan Kedakwahan, 2022)
This research is literature research that uses a qualitative descriptive approach with the title Al-Farabi's Philosophy About The Main Country (al-Madinah Al-Fadhilah). The data collected is in the form of reliable sources, such as journals, and books, with technical analysis of triangulation. the results of this study indicate that the concept of the main state according to al-Fabari is a country whose population is in happiness led by the Prophet or has prophetic nature, namely philosophers. because a philosopher has Fa'al reason and can connect it with his soul so that he can bring his people to the main goal, namely happiness.